A Rare Cutaneous Manifestation: Leukocytoclastic Vasculitis after Pfizer-BioNTech COVID-19 Vaccination - Yaritza Serrano Gomez; Brittney Grella; Hongbei Wang (Hindawi Limited, 2022)
There is growing evidence that vaccines against SARS-CoV-2 can cause various skin reactions, many of which have autoimmune origins. These specific vaccine-induced autoimmune conditions with cutaneous manifestations include lupus erythematosus, bullous pemphigoid, vitiligo, alopecia areata, and leukocytoclastic vasculitis (LCV). In particular, LCV, which is also called hypersensitivity vasculitis, is an inflammation of small blood vessels. We present a case of an 81-year-old male evaluated in the emergency department for a bilateral purpuric non-blanching rash that appeared ten days after receiving the Pfizer-BioNTech booster vaccine against SARS-CoV-2. Results of a skin biopsy indicated LCV, and the rash completely resolved three weeks after clinical presentation.